Sicily : land of love & strife - Spano, Mark, 1949-; Marcusceccu Investors LLC; Mark Spano Communications (Firm); Soundview Media Partners ([Chapel Hill, NC] : Marcusceccu Investors LLC : Mark Spano Communications, 2018)
This exploration of Sicily takes the viewer to a place of spectacular beauty, epic human struggle, depth and diversity of culture, philosophic insights, and historic sites.
Little has been produced about the cultural or historic relevance of Sicily. The most invaded place on the planet, the three-sided island rivals Greece and Egypt as a primary source for Western ideas. Sicily: Land of Love and Strife takes the viewer to a place more fascinating and more diverse than any other Italian region. This journey demonstrates that fewer places on the planet compare to Sicily for a story of spectacular beauty, epic human struggle, depth and diversity of culture, philosophic insights, and historic sites. Because of the island's great natural abundance and its strategic location in the Mediterranean-at the crossroads of Europe, Africa, and Asia-ownership of this rugged and fertile terrain has been contested for millennia. But except for its crime, Sicily has gone unexplored. The island's association with the Mafia, so deeply entrenched in popular consciousness, has obscured a more rounded and accurate depiction of its history and culture.
Originally released as a motion picture in 2016 as Reimagining Sicily.
Cinematographer, David Tyson ; editor, Larry Gardner ; original score, Fred Story.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 20, 2019)
Keywords: Sicily (Italy) -- Description and travel; Documentary films; Nonfiction films; Internet videos; Streaming video